Influence of intraoperative electromyographic changes and surgical extent on post-thyroidectomy esophageal motility: a prospective cohort study - Gunay, Mehmet; Iscan, Yalin; Sormaz, Ismail Cem; Aksakal, Nihat; Tunca, Fatih; Akyuz, Filiz; Giles Senyurek, Yasemin (Frontiers in Endocrinology, 2025)
BackgroundThyroidectomy may lead to postoperative swallowing difficulties. This study aimed to evaluate the relationship between electromyographic (EMG) changes observed during intraoperative neuromonitoring (IONM) and swallowing problems following lobectomy, total thyroidectomy (TTx), and total thyroidectomy with central lymph node dissection (TTx+CLND), as assessed using high-resolution manometry (HRM).MethodsThis prospective study included 36 patients who underwent thyroid lobectomy (n=9), TTx (n=15), or TTx+CLND (n=12) by using IONM. All patients were questioned about dysphagia and underwent HRM preoperatively and at postoperative 6th month. Demographic data, the dominant nodule size, total thyroid volume, IONM findings and HRM results were recorded. The pre-and postoperative changes in HRM results were evaluated according to the clinical characteristics, extent of surgery and IONM data.ResultsFive (14%) reported de novo postoperative dysphagia. No loss of signal during IONM and postoperative vocal cord palsy were observed. Adverse EMG changes and combined event (CE) occurred in 8 (22%) and 2 (5.5%) patients, respectively. Postoperative upper esophageal sphincter resting pressure (UESRP) significantly decreased from a median of 181 mmHg (range: 12–407 mmHg) to 109 mmHg (range: 8.6–407 mmHg), postoperatively (p=0.03). The percentage of UESRP decrease was 64% (range: -82_20%) and 25% (range: -86 _135%) in patients with and without postoperative de novo dysphagia (p=0.06). In the TTx group, which had significantly larger tumor size and higher thyroid volumes compared to the TTx+CLND group, UESRP decreased by 44%, versus 16% in the TTx+CLND group (p=0.001). Patients who experienced adverse EMG changes exhibited a significantly lower median percentage decrease in UESRP (-3%, range: -54% to 52%) than those without EMG abnormalities (-34%, range: -86% to 135%) (p=0.04). No significant correlation was found between the EMG changes in external branch of superior laryngeal nerve and postoperative UESRP alterations.ConclusionThis prospective clinical study demonstrated that UESRP decreases after thyroidectomy even in patients without IONM evidence of nerve injuries. Patients with large nodules, high thyroid volume, and new-onset dysphagia tended to show greater reductions in UESRP, whereas those with intraoperative adverse EMG changes exhibited less pronounced decreases. These heterogeneous responses may reflect complex neuromuscular adaptations involving the cricopharyngeus muscle.